2012
DOI: 10.1155/2012/798264
|View full text |Cite
|
Sign up to set email alerts
|

Extramedullary Plasmacytoma of the Pancreas: A Rare Entity

Abstract: Extramedullary plasmacytomas are plasma cell neoplasms in organs other than the bone marrow. Most are found in the upper respiratory tract. Involvement of the pancreas is rare. We report a case of pancreatic plasmacytoma in association with advanced multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…Radiotherapy is considered a plausible option for treating non-head-and-neck EMP as it achieves symptomatic control and is likely to be less toxic compared with surgery and chemotherapy [ 6 ]. Evidence of this fact is supported by individual cases in the literature although there are no clinical studies categorically confirming it [ 1 , 2 , 3 , 4 , 5 ]. In some cases, radiotherapy is given after the failure of previous treatments, but in those cases, cumulative toxicity may be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiotherapy is considered a plausible option for treating non-head-and-neck EMP as it achieves symptomatic control and is likely to be less toxic compared with surgery and chemotherapy [ 6 ]. Evidence of this fact is supported by individual cases in the literature although there are no clinical studies categorically confirming it [ 1 , 2 , 3 , 4 , 5 ]. In some cases, radiotherapy is given after the failure of previous treatments, but in those cases, cumulative toxicity may be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Solitary EMPs of the retroperitoneum are rare with few reports in the literature [ 2 ]. Plasma cell tumors tend to be radio- and chemosensitive; therefore, the treatment of choice for EMPs can either be surgery, chemotherapy or radiotherapy [ 3 ]. The best choice for treatment is not evident [ 2 ], but most cases are localized, and some studies have shown that radical radiotherapy offers potential local control and organ preservation associated with low toxicity [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies investigating the CT findings of EMPs in other organs were identified during the literature search for the present study. One study, which examined a case of pancreatic EMP, demonstrated a large homogeneously-enhancing mass in the region of the pancreatic head ( 9 ). A second study revealed a well-demarcated, minimally homogeneously-enhancing, 1.5×1.0×1.2-cm mass in the left arytenoid region of the larynx ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pancreas is rarely infiltrated by plasma cells as an EMP, and obstructive jaundice is also rarely diagnosed as a result of plasma cell neoplasms (2). Only 25 cases have been reported in the English literature to date (3). We reported a case of pancreatic plasmacytoma presenting with obstructive jaundice.…”
Section: Introductionmentioning
confidence: 92%